2013
DOI: 10.1007/s10140-013-1121-0
|View full text |Cite
|
Sign up to set email alerts
|

Cruciate ligament avulsion fractures: Anatomy, biomechanics, injury patterns, and approach to management

Abstract: Injury to the ACL or PCL of the knee most commonly involves a tear of the collagenous fibers of the ligament. Less frequently, a cruciate ligament injury involves an avulsion fracture at the origin or insertion of the ligament, usually from the insertion site on the tibial surface. Avulsion fractures of the cruciate ligaments are important, as they can be identified on radiographs, allowing a specific diagnosis. Although more common in children, when they occur in adults, they are more commonly associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 42 publications
0
40
0
4
Order By: Relevance
“…Many times it is difficult to estimate the size of the main fragment or degree of comminution, particularly in the absence of computed tomography, which is of great assistance in treatment planning for this type of injury. 11 Therefore, the choice of the treatment will depend on the possibility of fixating the fragment. The more fragile the avulsed fragment, the more important it is to find an appropriate and precise approach angle for inserting the fixation device.…”
Section: Discussionmentioning
confidence: 99%
“…Many times it is difficult to estimate the size of the main fragment or degree of comminution, particularly in the absence of computed tomography, which is of great assistance in treatment planning for this type of injury. 11 Therefore, the choice of the treatment will depend on the possibility of fixating the fragment. The more fragile the avulsed fragment, the more important it is to find an appropriate and precise approach angle for inserting the fixation device.…”
Section: Discussionmentioning
confidence: 99%
“…1,11 As mentioned earlier, their management has evolved from traditional open or mini-open techniques to completely arthroscopic techniques using sutures, screws, wires, anchors, or even buttons. 4,[6][7][8][9][10] When all previous methods are compared, screw fixation seems to have the most equivocal outcomes. Biomechanical studies have shown divergent results regarding ultimate failure rates and fragment displacement, whereas reoperation for hardware removal, possible loss of extension, fracture fragmentation, and residual anteroposterior or rotational instability remain serious concerns.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Various fixation methods using screws, wires, anchors, or even "buttons" have been extensively described in the English-language literature with very promising results. 1,4,[6][7][8][9][10] Among them, suture fixation techniques appear to be the most popular, as well as the most "user-friendly," among orthopaedic surgeons. 1 However, concerns have been raised regarding potential intraoperative complications, difficulties of suture passage, and prolonged operative times.…”
mentioning
confidence: 99%
“…Sie beschreibt 4 Subtypen, wobei Typ 1 nicht disloziert ist und Typ 4 eine dislozierte Mehrfragmentavulsion des VKB darstellt. Die knöcher-nen HKB-Ausrisse werden in 3 Typen -nicht disloziert, disloziert mit Kontakt des Fragmentes zurproximalenTibia und komplett disloziert -unterteilt [4,17].…”
Section: Klassifikationenunclassified